2001
DOI: 10.1099/00207713-51-4-1505
|View full text |Cite
|
Sign up to set email alerts
|

Pseudonocardia kongjuensis sp. nov., isolated from a gold mine cave.

Abstract: The taxonomic position of an isolate that was recovered from a gold mine cave near Kongju, Republic of Korea, was determined by 16S rDNA sequence studies and chemotaxonomic characterization. Comparative studies of 16S rDNA sequences indicated that this organism was phylogenetically related to members of the genus Pseudonocardia, branching outside a cluster encompassing Pseudonocardia autotrophica and Pseudonocardia compacta. The affiliation to the genus was also supported by the cell chemistry, which was repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
32
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 16 publications
(17 reference statements)
0
32
0
Order By: Relevance
“…Phospholipid composition has been used as a key chemotaxonomic marker in the delineation of actinomycete genera or genus groups (Lechevalier et al, 1977). However, there are reports of phospholipid profiles varying according to species (Xu et al, 1999;Lee et al, 2001). The differentiating characteristics of the isolate and the type species of the genus Blastococcus are given in Table 1.…”
mentioning
confidence: 99%
“…Phospholipid composition has been used as a key chemotaxonomic marker in the delineation of actinomycete genera or genus groups (Lechevalier et al, 1977). However, there are reports of phospholipid profiles varying according to species (Xu et al, 1999;Lee et al, 2001). The differentiating characteristics of the isolate and the type species of the genus Blastococcus are given in Table 1.…”
mentioning
confidence: 99%
“…Furthermore, moderate amounts of phosphatidylglycerol, an unknown lipid, L1, and small or trace amounts of phosphatidylinositol, phosphatidylinositol-mannoside, three unknown lipids, two unknown phospholipids and four unknown glycolipids were detected. The presence of phosphatidylcholine attributes phospholipid type PIII to strain 04-St-002 T (Lechevalier et al, 1977) which has been reported for several Pseudonocardia species, including Pseudonocardia compacta, P. alni, P. antarctica, Pseudonocardia ammonioxydans, Pseudonocardia kongjuensis and Pseudonocardia spinosispora (Henssen et al, 1983;Evtushenko et al, 1989;Lee et al, 2001Lee et al, , 2002Prabahar et al, 2004;. Another species, Pseudonocardia ailaonensis, for which phospholipid type PIII was reported might be erroneously allocated to this phospholipid type because the authors did not report the presence of phosphatidylcholine (Qin et al, 2008).…”
mentioning
confidence: 98%
“…nov. is proposed. The type strain is 04-St-002 T (5DSM 45256 T 5CCM 7582 T ).The genus Pseudonocardia, originally proposed by Henssen (1957) for nocardioform actinomycetes that lack mycolate and have a type IV cell wall, reflected by the presence of meso-diaminopimelic acid and the sugars arabinose and galactose (Lechevalier & Lechevalier, 1980), comprises 28 species at the time of writing (Gu et al, 2006; Huang et al, 2002;Lee et al, 2000Lee et al, , 2001Lee et al, , 2002Lee et al, , 2004 Kämpfer & Kroppenstedt, 2004;Liu et al, 2006; Mahendra & AlvarezCohen, 2005;Qin et al, 2008).Strain 04-St-002 T was isolated from a wall colonized with moulds. After extraction of 1 g material sample for 15 min in 10 ml 0.9 % NaCl solution containing 0.01 % (v/v) Tween 80 and dilution on M79 agar (containing 10 g glucose, 10 g Bacto peptone, 2 g casein hydrolysate, 2 g yeast extract, 6 g NaCl, 15 g agar) for 2 weeks at 28 u C, the strain was maintained on M79 at 28 u C and showed a brown-coloured substrate mycelium.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At the time of writing, the genus contains 27 species with validly published names. Strains have been isolated from a wide range of habitats such as treebark compost (Reichert et al, 1998), a gold mine (Lee et al, 2001), industrial sludge contaminated with 1,4-dioxane (Mahendra & Alvarez-Cohen, 2005) and coastal sediment . The most recently reported species was Pseudonocardia oroxyli, which was isolated from surfacesterilized roots of the higher plant Oroxylum indicum (Gu et al, 2006).…”
mentioning
confidence: 99%